Cerita Rakyat “Koda Ragamp” dari Dayak Simpakng dan Cinta Kasih Kristiani - Doni, Antonius (Perspektif, 2013)
True love is so dear in human life and it is exactly the highly regarded quality both for each individual person and for communal life. The folklore of “Koda Ragamp” of Dayak Simpakng (Kalimantan) narrates the true and sacrificing love of a mother to her own son, even though the son shows his disobedience and unfaithfulness to his mother and treats her so badly. The writer reflects theologically this folklore and adopts it as a possible and suitable method in developing a so-called narrative theology, popular catechism, and contextual ministry. The writer also argues that the true love of Koda Ragamp’s mother intrinsically reflects the Christian love, namely, a sacrificing love whithout reserve.